An Analysis of Loan Loss Provisioning Behaviors in Chinese Banking - Luan, Jia-Ni (2017)
The managerial behaviors of loan loss provisions (LLPs) are generally associated with earnings management, capital management, and pro-cyclical behavior. The aim of this study is to investigate LLPs behaviors in Chinese banks from 2010 to 2016. Since China plays a vital role in the development of global economy, studying the mechanism of loan loss provisioning management is necessary. The hypotheses of income smoothing, capital management, pro-cyclical behavior and correlation between banks’ efficiency and LLPs are tested through collecting a sample of 73 publicity listed banks, using the Stochastic Frontier Analysis (SFA) and the System Generalized Method of Moments (GMM). The empirical results imply that Chinese banks’ managers are likely to manipulate income through LLPs while no evidence supports for the capital management hypothesis. In addition, the management of LLPs in China presents the pro-cyclicality, which indicates that Chinese banks may reduce LLPs during the economy booming. This study also tests the correlation between banks’ efficiency and LLPs. The results imply that poor management in banks’ cost may cause the decline in LLPs.